Workplace Relations and Opportunities for Career Development Impact the Retention of Veterinarians in Shelter Medicine - Powell, Lauren; Reinhard, Chelsea L.; Serpell, James; Watson, Brittany (Frontiers in Veterinary Science, 2021)
Shelter medicine has grown considerably over recent years with many shelters hiring veterinarians for the first time or expanding their veterinary teams. As a result, there is a dearth of shelter veterinarians and retention has become a key concern for the field. The goal of this study was to describe veterinarians’ perceptions of shelter medicine, and their feelings of job satisfaction, loneliness, and professional fulfillment. The sample included 52 shelter veterinarians, 39 previous shelter veterinarians and 130 non-shelter veterinarians (n=221) who each completed an online survey. Current and previous shelter veterinarians had comparable perceptions regarding the appeal of most shelter medicine duties, although there were differences in the duties they performed within their job. More current shelter veterinarians participated in population management, policy development, administrative duties, and decision-making for individual patients (euthanasia, treatment, and adoptability). Considering other employment attributes, we found previous shelter veterinarians had lower mean rankings than current and non-shelter veterinarians regarding their interactions with administrative staff, ability to be part of a multiple veterinarian team and the availability of mentorship. Loneliness and professional fulfillment were mostly comparable between the groups, although previous shelter veterinarians were more likely to report they felt unhappy (X2=16.60, p=0.02) and left out at work (X2=12.43, p=0.02). Our findings suggest veterinarians who participate in decision-making for patients and shelter management procedures may be more willing to continue working in shelter medicine. Animal shelters should also employ strategies to improve workplace relationships and offer career development opportunities to improve job satisfaction and retention of veterinarians within the field.